Verteilungsformen der Einlagenbestände auf Sparkonten - Bernhard Korte; Walter Oberhofer (Kredit und Kapital, 1970)
Forms of Distribution of Savings Account Deposits Analyses of savings account deposits have hitherto been limited essentially to investigations of average values. Predications as to the form of distribution, i.e. as to the distribution function and its parameters, could not be derived from those analyses. On the basis of comprehensive empirical material, this study shows that the deposits on savings accounts satisfy the conditions of a mixed distribution comprising two log-normal distributions. For savings deposits this verifies a predication analogous to Gibrat's law of personal income distribution. Furthermore, the two components of the mixed distribution characteriza a group of small savers and one of big savers. The investigations have shown that these groups are relatively disjunct, remain almost constant over time and manifest little mutual permeability. In addation, for certain subgroups of savers defined by social criteria the study examines in what ratio they are distributed between the two components of the mixed distribution, i. e. to what extent hese subgroups belong to the small or big savers.
Keywords: 330